Fração de filme em lavadores Venturi - Guerra, Andressa Pinheiro (2010)
Venturi scrubber is an equipment applied to particulate material removal, soluble gases absorption, and gas stream odors reduction. This device utilizes of a liquid wash that collides a high velocity gas inside the scrubber. Liquid is then atomized, producing drops, which collect the particles. During the process, part of the drops retain at scrubber walls as a film. The referred film increases pressure drop, affecting efficiency. Our study aim, by observing the film fraction, was to reduce the pressure loss, increasing the scrubber efficiency, and lowering operational costs. Two Pease-Anthony circular transverse-section scrubbers, vertically set, were used. In order to obtain more information on the film fraction influence to the scrubber performance, some features such as dimensionless axial distance to the injection point, convergence angle, number of injection points, and throat diameter, were varied. Gas velocities used were 50, 70, and 90 m/s, as for jet penetration, 5% to 85%. Film fraction has varied to liquid jet penetration, and has shown a interval of minimal film formation on scrubber walls, to each specific configuration. Largest quantities of film were collected on the lower and higher jet penetrations. Liquid fraction on the scrubber walls has also varied to the gas velocity, liquid injection orifices configuration, dimensionless axial distance from the injection point, and throat diameter The convergence section angle, however, has not influenced the film fraction variation in any of the studied conditions, in terms of the jet penetration. A different behavior among the angles, were only obtained with the gas velocity. Different orifice configurations, under excessive penetrations, have changed the jet trajectory.